Comparison of Breast Cancer Aggressiveness in Young and Older Patients - Remisha Zahid Shah, Samina Qamar, Shahida Niazi, Madiha Ehsan, Nazia Noor, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare aggressiveness of breast cancer in young and old patients. Study Design: Cross-sectional Place and Duration of Study: Department of Histopathology, King Edward Medical University, Lahore from 1st January 2016 to 31st December 2018. Methodology: One hundred and fifty women were divided into young (<40 years) and adult (>40 years) group depending upon their age. Women with breast cancer within 20-80 years were enrolled. Modified Radical-Mastectomy specimens as well as lumpectomy having axillary-clearance were sent to pathological laboratory. Biopsies were fixed in formalin in addition to hematoxylin, eosin staining. Data was documented and aggressiveness of breast cancer within both groups was evaluated on the basis of factors as tumor size, tumor type, lymph nodes, metastasis, tumor staging and tumor grading. Results: A significant variance in young and adult cases tumor grade, lymph node involvement and tumor size. The young patients had 12.90% cases of metastasis than old only having 4.5% (p<0.05). Similarly high tumor stage and aggressive tumors were also seen in young patients when compared with old. Conclusion: Young patients with breast cancer are more prone towards aggressive carcinoma than older patients.